Histochemistry and Protein Profile of The Venom Glands of Workers of Neoponera villosa Ants (Hymenoptera: Ponerinae) - Henrique, Leopoldo Heitor [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (California State University, 2011)
Cytochemical and histochemical tests applied to the venom glands of Neoponera villosa worker ants showed the presence of specific elements, such as lipids, polysaccharides (including glycogen), total protein, RNA, DNA and nucleolus organized regions (NORs). It was observed that protein is the most abundant element, since all portions of the gland reacted with strong positivity to the bromophenol blue test, especially the secretion, revealing the protein characteristics of the venom. Lipids were also present throughout the majority of the venom glands. The polysaccharides were more evident within the cells of the convoluted gland. The secretion, meanwhile, showed a weak positive reaction to this test. Despite the large number of protein elements in the secretion, was observed that the protein is not always in free form and is often associated with other elements, probably forming complexes. Tests to demonstrate RNA, DNA and NORs showed intense cell activity along the different portions of the gland and showed different stages of cell cycles. Tests for the dosage of protein in individuals collected in the summer (February-March) and winter (August-September) showed that there are differences in the total concentration of protein in the glands. Proteins with different molecular weights were detected in the final secreted product.
Keywords: ants; electrophoresis; lipids; polysaccharides; Ponerinae; proteins; venom glands